Socio- Cultural Variables Of Congenital Malformation In Newborns - Khan Zulfia; Pattnayak U; Ahmed A.J; Zaheer M (Wolters Kluwer Medknow Publications, 1997)
Research question: Is there an association between common socio â€" cultural variables and congenital malformation? Objectives: To determine the rate of congenital malformation at birth in hospital deliveries and its association with socio- cultural factors. Study design : Cross- sectional. Setting: J.N. Medical College Hospital and Mohanlal Gautam Rajkiya Hahila Chikitsalaya (District hospital), Aligarh. Participants: All newborn babies (including still births) delivered in the two hospitals and their mothers. Study variables: Social class, religion, consanguinity of marriage, age of mother, parity, urban rural status, history of viral illness, drug intake and tobacco use during pregnancy. Outcome variables: Congenital malformations at birth. Statistical analysis: Chi- square test. Results: The overall prevalence of congenital malformations was 2.8%, being 1.6% in live births and 15.6% in stillbirths. Social class, consanguinity of marriage, parity, urban or rural status and history of viral illness during pregnancy were significantly associated with the date of congenital malformation. Conclusion: Certain socio- cultural factors are associated with congenital malformations and can be used in screening during ante- natal period.